The return of depression economics and the crisis of 2008 - Krugman Paul (London : Penguin, 2008)
Shows how crisis parallels the events that caused the Great Depression - and explains what it will take to avoid catastrophe. In this book, the author surveys the economic crises that had swept across Asia and Latin America, and warns that those crises were a warning for all of us.
Includes index.
nmn 30/07/13
Loans
Keywords: Business cycles; Recessions -- History -- 21st century. Business cycles -- History -- 21st century; Financial crises -- - History -- 21st century; Depressions -- 1929.; Recessions